2021
DOI: 10.1186/s40780-021-00207-w
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin absorption decreased independently of P-gp activity in rats with irinotecan-induced gastrointestinal damage

Abstract: Background Irinotecan (CPT-11) is clinically known to cause severe diarrhea and gastrointestinal damage. Recently, we have reported that CPT-11-induced gastrointestinal damage is associated with the upregulation of intestinal P-glycoprotein (P-gp) expression and decreased absorption of its substrate, dabigatran etexilate (DABE), using a rat model. However, the P-gp activity or its contribution to the decreased absorption remains unclear. The aim of this study was to quantitatively evaluate how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Indeed, Gly‐Sar decreased the gastrointestinal absorption of CEX by only ∼10%, suggesting that CEX is absorbed primarily by passive diffusion. We previously reported that irinotecan‐induced gastrointestinal damage in rats reduced the absorption rate of orally administered acetaminophen, a passive marker (Hattori et al., 2019), and the intestinal absorption of digoxin, a P‐gp substrate, administered with a P‐gp inhibitor, clarithromycin (Tsuchitani et al., 2021). Furthermore, in this study the decrease in BA of CEX by Gly‐Sar coadministration was similar between the irinotecan and the control groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Gly‐Sar decreased the gastrointestinal absorption of CEX by only ∼10%, suggesting that CEX is absorbed primarily by passive diffusion. We previously reported that irinotecan‐induced gastrointestinal damage in rats reduced the absorption rate of orally administered acetaminophen, a passive marker (Hattori et al., 2019), and the intestinal absorption of digoxin, a P‐gp substrate, administered with a P‐gp inhibitor, clarithromycin (Tsuchitani et al., 2021). Furthermore, in this study the decrease in BA of CEX by Gly‐Sar coadministration was similar between the irinotecan and the control groups.…”
Section: Discussionmentioning
confidence: 99%
“…In rats with irinotecan-or 5-FU-induced gastrointestinal damage, we found more than an 80% decrease in the bioavailability (BA) of dabigatran etexilate, a P-gp substrate, while the expression of P-gp increased in the upper intestine (Hattori et al, 2019;Tsujii et al, 2018;Yotsumoto et al, 2017). Furthermore, we reported that the gastrointestinal absorption of digoxin, a typical P-gp substrate, decreased in rats with irinotecan-induced gastrointestinal damage (Tsuchitani et al, 2021).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The determination of digoxin and digitoxin levels by LC-MS/MS was conducted according to a method previously reported by our group. 33) The concentrations of fexofenadine and digoxin were determined using an LC-MS/MS system consisting of a controller (CBM-20A, Shimadzu, Kyoto, Japan), a pump (LC-20AD, Shimadzu), a triple quadrupole mass spectrometer (LCMS-8050 or LCMS-8030, Shimadzu), and a column oven (CTO-20AC, Shimadzu). To determine the concentration of fexofenadine in a sample, the sample was separated using an octadecylsilane column (150×2.0 mm, 5C 18 -MS-II, Cosmosil, Nacalai Tesque) equipped with a guard column (50 × 2.0 mm, 5C 18 -MS-II, Cosmosil).…”
Section: Determination Of Fexofenadine and Digoxin Concentrations Usi...mentioning
confidence: 99%